2015
DOI: 10.1371/journal.pone.0144878
|View full text |Cite
|
Sign up to set email alerts
|

A Side by Side Comparison of Bruker Biotyper and VITEK MS: Utility of MALDI-TOF MS Technology for Microorganism Identification in a Public Health Reference Laboratory

Abstract: Matrix-assisted laser desorption ionization–time of flight mass spectrometry (MALDI-TOF MS) has emerged as a rapid, highly accurate, and cost-effective method for routine identification of a wide range of microorganisms. We carried out a side by side comparative evaluation of the performance of Bruker Biotyper versus VITEK MS for identification of a large and diverse collection of microorganisms. Most difficult and/or unusual microorganisms, as well as commonly encountered microorganisms were selected, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
102
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(105 citation statements)
references
References 31 publications
1
102
0
2
Order By: Relevance
“…Identification of mycobacteria has not reached an optimal level of routine testing yet and published studies showed discrepant performances, depending on spectrometer, extraction method, algorithm, library, media, and biomass used for the assays (15)(16)(17)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32). In this study, we compared two distinct databases of Vitek-MS, the Saramis v4.12 open database and the new IVD v3.0 closed database.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Identification of mycobacteria has not reached an optimal level of routine testing yet and published studies showed discrepant performances, depending on spectrometer, extraction method, algorithm, library, media, and biomass used for the assays (15)(16)(17)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32). In this study, we compared two distinct databases of Vitek-MS, the Saramis v4.12 open database and the new IVD v3.0 closed database.…”
Section: Discussionmentioning
confidence: 99%
“…It was initially evaluated with mycobacterial intact cells (9)(10)(11)(12), but several investigators worked on improving inactivation and protein extraction (13)(14)(15)(16)(17)(18)(19)(20). Most published studies assessed the performance of MALDI-TOF BioTyper (Bruker Daltonics, Bremen, Germany) (15,17,(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31). Few of them evaluated Vitek MS (bioMérieux, Marcy l'Etoile, France) (16,17,20,24,25,32).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, when present in their respective databases, 76.7% (33/43) and 50.0% (10/20) of isolates could be correctly identified (to both the species and genus levels) with the Bruker Biotyper and Vitek MS systems, respectively; only one misidentification was obtained (1 Fusarium proliferatum isolate misidentified as Fusarium oxysporum) with the Vitek MS system, whereas there was no misidentification with the Bruker Biotyper system. When absent from their respective databases, 12 misidentifications (mainly to the genus level) were obtained with the Vitek MS system, as opposed to none with the Bruker Biotyper system (21).…”
mentioning
confidence: 99%
“…In a head-to-head comparison of the Bruker Biotyper and Vitek MS systems carried out on a large collection of microorganisms, including filamentous fungi, at a public health reference laboratory in Québec, Canada, it was found that only 17 of 71 isolates tested were referenced in both systems' databases, with 43 being present in the Bruker Biotyper database and 20 being present in the Vitek MS database (21). Thus, when present in their respective databases, 76.7% (33/43) and 50.0% (10/20) of isolates could be correctly identified (to both the species and genus levels) with the Bruker Biotyper and Vitek MS systems, respectively; only one misidentification was obtained (1 Fusarium proliferatum isolate misidentified as Fusarium oxysporum) with the Vitek MS system, whereas there was no misidentification with the Bruker Biotyper system.…”
mentioning
confidence: 99%